Mitigating Learning Loss and Accelerating Learning Recovery through New Learning Strategies in TEFL - Zumrotul Fauziah; Sri Minarti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
In the post-pandemic era, many Indonesian students suffer learning loss. After the government allows the schools to have offline learning, teachers and lecturers should do acceleration for learning recovery. This study is aimed to describe strategies used by English lecturers to recover learning loss. This study is a descriptive qualitative study that focuses on English lectures at higher education levels. The data was collected through semi-structured interviews with some English lecturers who teach in the English education department and other departments at several universities in Indonesia. The technique of data analysis includes data reduction, data display, conclusion drawing, and data validation through triangulation technique from data resources. The result shows that there are four strategies that used by the lecturers to mitigate learning loss and accelerate learning recovery for EFL learners, they are teaching using more interesting and various teaching strategies, such as Drill and Practise method to improve vocabulary mastery, promoting autonomous and cooperative learning, designing joyful learning activities, and implementing project-based learning. Therefore, lecturers perceive that to accelerate learning recovery, lecturers should provide more time, energy, and strategies to catch up with the learning loss suffered by students.